Microenvironment‐Protected Exosome‐Hydrogel for Facilitating Endometrial Regeneration, Fertility Restoration, and Live Birth of Offspring. Issue 11 (16th February 2021) - Lin, Jiaying; Wang, Zhen; Huang, Jialyu; Tang, Shengluan; Saiding, Qimanguli; Zhu, Qianqian; Cui, Wenguo
Abstract: Thin endometrium is a primary cause of failed embryo transfer, resulting in long‐term infertility and negative family outcomes. While hormonal treatments have greatly improved fertility results for some women, these responses remain unsatisfactory due to damage and infection of the complex endometrial microenvironment. In this study, a multifunctional microenvironment‐protected exosome‐hydrogel is designed for facilitating endometrial regeneration and fertility restoration via in situ microinjection and endometrial regeneration. This exosome hydrogel is formulated via Ag + ‐S dynamic coordination and fusion with adipose stem cell‐derived exosomes (ADSC‐exo), yielding an injectable preparation that is sufficient to mitigate infection risk while also possessing the antigenic contents and paracrine signaling activity of the ADSC source cells, enabling regeneration of the endometrial microenvironment. In vitro, this exosome‐hydrogel exerts an outstanding neovascularization‐promoting effect, increased human umbilical vein endothelial cell proliferation and tube formation for 1.87 and 2.2 folds. In vivo, microenvironment‐protected exosome‐hydrogel also reveals to promote neovascularization and tissue regeneration while suppressing local tissue fibrosis. Importantly, regenerated endometrial tissue is more receptive to give embryos and birth to a healthy newborn. This microenvironment‐protected exosome‐hydrogel system offers a convenient, safe, and noninvasive approach for repairing thin endometrium and fertility restoration. Abstract : An injectable adipose derived stem cell‐exosome hydrogel is developed through Ag + ‐S dynamic coordination and fusion with ADSC‐exos, that is able to promote neovascularization and endometrial tissue regeneration. Local injection of this exosome‐hydrogel is sufficient to restore fertility and improve pregnancy and birth rates, indicating that this ADSC‐exo hydrogel warrants further pharmaceutical development in anticipation of its future clinical use.